The Dynamics of Secondary Rules in Constitutional Adjudication: An Analysis of H.L.A. Hart’s Theory on Indonesia’s Constitutional Court Decision Number 90/PUU-XXI/2023 - Salman Alfarisi; Najwa Hanif Artfian Arrasyid Aulia Putra; Primerta Putri Hapsari; Martitah Martitah; Dewi Sulistianingsih (The Indonesian Journal of International Clinical Legal Education, 2026)
This study aims to examine the constitutional validity and theoretical implications of Constitutional Court Decision Number 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates in Indonesia. The main issues raised are the inconsistency of legal reasoning and the shift in the role of the Constitutional Court, which acts as a positive legislator, triggering a substantive legitimacy crisis behind formal validity. The research method employed is a juridical-normative approach with a qualitative doctrinal orientation. The analysis was conducted using H.L.A. Hart’s theoretical instrument regarding the dual rule system to dissect the relationship between primary and secondary rules. The research findings indicate that procedurally, the decision is a valid application of the rule of adjudication and the rule of change, as it is sourced from the highest rule of recognition, namely the 1945 Constitution. However, a substantial rift exists between the internal aspects of legal authority and the external aspects of public acceptance due to the open-ended nature of the legal language used by the judge. This study concludes that although the decision has binding legal force, this phenomenon indicates an expansion of secondary authority that can threaten legal certainty if not limited by objective parameters. The results of this study contribute to clinical legal education by enhancing understanding of the dynamics of norm change through judicial channels during the democratic transition process.